Comparative Legal Context of Land Consolidation in Georgia - Merebashvili, Tornike (European Scientific Journal, ESJ, 2023)
From the time of independence to the present day, land legislation in Georgia has undergone numerous changes, evolving at its own pace. However, Georgia’s aspiration to join the European Union necessitates additional modifications. This article focuses on one specific issue: land consolidation. The analysis is conducted through comparative legal and historical-toponymic research, drawing insights from similar countries such as Hungary, Slovakia, and other European states. This approach is justified by the small size of these countries, their recent history of joining the European Union, and ongoing reforms in land consolidation. The topic’s relevance and outcome orientation are highlighted, as land consolidation significantly intertwines with public and private legal interests. The article encompasses scrutiny of Georgian and foreign legislative acts, doctrinal materials, and other historical sources. Land consolidation stands out as a pivotal element in the broader context of land law and, more practically, as the primary driver for the functioning of the agricultural sector, the country’s development, and its path toward European Union membership. In essence, this article evaluates Georgia’s capacity to establish an effective policy and legislative framework to regulate these relationships.